Punkzilla - Rapp, Adam (Somerville, Mass. : Candlewick Press, 2009)
A runaway boy nicknamed Punkzilla who sustains himself on the streets of Portland through petty crimes decides to try to kick his meth habit, turn his life around, and go on a journey to Tennessee to visit his dying older brother.
Keywords: Runaway teenagers -- Fiction; Voyages and travels -- Fiction; Brothers -- Fiction; Fiction